2022
DOI: 10.1177/19417381221123517
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Knee-related Quality of Life With Function, Psychological Factors, Strength, Performance, and Postural Stability After ACL Reconstruction: A Cross-Sectional Study

Abstract: Background: Patients after anterior cruciate ligament reconstruction (ACLR) have decreased health-related quality of life (QoL) compared with healthy control participants. Few studies have verified the predictors of QoL using Quality of Life Outcome Measure Questionnaire for Chronic Anterior Cruciate Ligament Deficiency (ACL-QoL), and no study has verified the relationship of psychological factors and knee function with ACL-QoL in patients after ACLR. Hypothesis: Knee functional status, muscle strength, perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Due to the importance that kinesiophobia has on the outcomes of chronic AT patients, it may be important for clinicians to be able to identify this phenomenon in patients and recommend psychologically informed physical therapy. It is possible that a comprehensive psychological assessment of patients may contribute to the process of shared decision‐making for the treatment of injuries with equivocal treatments [23, 35]. Findings from this paper can be useful in initiating the discussion of the role of kinesiophobia in other debilitating foot and ankle conditions, such as Lisfranc fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance that kinesiophobia has on the outcomes of chronic AT patients, it may be important for clinicians to be able to identify this phenomenon in patients and recommend psychologically informed physical therapy. It is possible that a comprehensive psychological assessment of patients may contribute to the process of shared decision‐making for the treatment of injuries with equivocal treatments [23, 35]. Findings from this paper can be useful in initiating the discussion of the role of kinesiophobia in other debilitating foot and ankle conditions, such as Lisfranc fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous paper using the same cohort of patients 6 months following ACL surgery, patients with higher ACL-RSI scores reported better functional and clinical outcomes and improved vertical jump performance at 6 months following ACL surgery [ 18 ]. Conversely, Tavares et al investigated health-related quality of life following ACL reconstruction and found few to no correlations between this variable and performance in hop tests [ 21 ]. Reporting on 303 patients up to 12 months after ACL reconstruction, Gauthier et al failed to find any correlation between psychological readiness to return to sport and functional ability [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, despite evidence of high rates of osteoarthritis after ACLR, the psychosocial impacts on the progression of health-related quality of life and osteoarthritis is under evaluation. 64,72 It appears mental recovery takes several years, possibly decades, and further investigation is needed to fully understand the directionality of these relationships and long-term associations.…”
Section: Relationship Between Psychosocial Measures and Physical Func...mentioning
confidence: 99%